2022
DOI: 10.31744/einstein_journal/2022ao6953
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of worse outcome for hospitalized COVID-19 patients, with emphasis on chest computed tomography data: a retrospective study

Abstract: Objective: To evaluate anthropometric and clinical data, muscle mass, subcutaneous fat, spine bone mineral density, extent of acute pulmonary disease related to COVID-19, quantification of pulmonary emphysema, coronary calcium, and hepatic steatosis using chest computed tomography of hospitalized patients with confirmed diagnosis of COVID-19 pneumonia and verify its association with disease severity. Methods: A total of 123 adults hospitalized due to COVID-19 pneumonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Using BIA, FFM ( 39 ) and ALST ( 38 ) were unrelated to severe COVID-19 in 2 studies. Lower muscle radiodensity was related to a greater likelihood of severe illness, including need for MV and/or greater disease severity in 5 studies ( 51 , 62 , 63 , 87 , 88 ), and unrelated/mixed findings were found in 6 studies ( 4 , 58 , 60 , 81 , 83 , 98 ). In addition, one study showed that increased muscle radiodensity was protective against MV or death (as a composite score) ( 74 ).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Using BIA, FFM ( 39 ) and ALST ( 38 ) were unrelated to severe COVID-19 in 2 studies. Lower muscle radiodensity was related to a greater likelihood of severe illness, including need for MV and/or greater disease severity in 5 studies ( 51 , 62 , 63 , 87 , 88 ), and unrelated/mixed findings were found in 6 studies ( 4 , 58 , 60 , 81 , 83 , 98 ). In addition, one study showed that increased muscle radiodensity was protective against MV or death (as a composite score) ( 74 ).…”
Section: Resultsmentioning
confidence: 91%
“…Seven studies found a positive association between these clinical outcomes and VAT ( 20 , 47 , 74 , 85 , 92 , 94 ), IMAT ( 62 , 74 ), SAT ( 85 ) and TAT ( 74 , 85 , 94 ). Conflicting findings were reported between adipose tissue (VAT, TAT, SAT and IMAT) and COVID-19 severity ( 6 , 20 , 58 , 62 , 92 , 96 , 98 ). Fat mass by BIA was positively related to COVID-19 severity ( 38 , 39 ) but inversely with complications ( 93 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations